The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1002/ppul.26328
|View full text |Cite
|
Sign up to set email alerts
|

Sociodemographic factors associated with tracheostomy and mortality in bronchopulmonary dysplasia

Abstract: Objectives: We sought to investigate how race, ethnicity, and socioeconomic status relate to tracheostomy insertion and post-tracheostomy mortality among infants with bronchopulmonary dysplasia (BPD). Methods: The Vizient Clinical Database/Resource Manager was queried to identify infants born ≤32 weeks with BPD admitted to US hospitals from January 2012 to December 2020. Markers of socioeconomic status were linked to patient records from the Agency for Healthcare Research and Quality's Social Determinants of H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…Racial influence on pediatric tracheostomy outcomes has previously been documented with black children undergoing higher rates of tracheostomy and higher comorbidity burden compared to white or Hispanic children. 42,43 However, there was no difference seen in rates of decannulation or mortality after tracheostomy. 42,43 The difference in decannulation rates between white children and other racial or ethnic groups in our cohort highlights potential health disparities and the impact of social determinants of health on comorbidity burden.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Racial influence on pediatric tracheostomy outcomes has previously been documented with black children undergoing higher rates of tracheostomy and higher comorbidity burden compared to white or Hispanic children. 42,43 However, there was no difference seen in rates of decannulation or mortality after tracheostomy. 42,43 The difference in decannulation rates between white children and other racial or ethnic groups in our cohort highlights potential health disparities and the impact of social determinants of health on comorbidity burden.…”
Section: Discussionmentioning
confidence: 98%
“…42,43 However, there was no difference seen in rates of decannulation or mortality after tracheostomy. 42,43 The difference in decannulation rates between white children and other racial or ethnic groups in our cohort highlights potential health disparities and the impact of social determinants of health on comorbidity burden. Further research is needed to assess for any differences in treatment efficacy among racial and ethnic groups including the associated socioeconomic influences and implicit biases.…”
Section: Discussionmentioning
confidence: 98%
“…Some studies have reported the mortality rates from the time of tracheostomy to the time of initial hospital discharge with a range of 9–23% [ 11 , 12 ]. Other studies report a combined mortality rate from the time of tracheostomy placement to a specified amount of time in the outpatient setting, and the available evidence on mortality rates in patients that received a tracheostomy for BPD is described in Table 1 [ 6 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ]. In summary, the answer to the question “what are the chances that my child will survive into adulthood and beyond, like other children?” seems to be that there is a chance somewhere from 74% to 93% that a baby who receives a tracheostomy for BPD will survive their initial hospitalization and childhood.…”
Section: Outcomes Following Tracheostomymentioning
confidence: 99%
“…In addition, those receiving public insurance had an increased rate of tracheostomy placement with longer length of hospital stay. Of note, there was no increased mortality among Black or Latinx patients or those with public insurance 10 . Those with the most limited access to care are, unfortunately, often those who need it most to ensure safety at home.…”
mentioning
confidence: 91%
“…Of note, there was no increased mortality among Black or Latinx patients or those with public insurance. 10 Those with the most limited access to care are, unfortunately, often those who need it most to ensure safety at home. In a world of increasing healthcare disparities, we feel strongly that care for these patients should be consistent and equitable.…”
mentioning
confidence: 99%